Diversity and bioactive potential of novel actinobacteria isolated from marine sediment in Pulau Tioman / Ng Zoe Yi - Ng , Zoe Yi (2019)
Tioman Island is one of many sources for underexplored actinobacterial diversity in Malaysia. Selective isolation, molecular profiling, 16S rRNA gene sequencing and phylogenetic analyses were carried out to highlight the diversity of the marine actinobacterial community in sediment samples collected off Tioman Island. A high number of diverse actinobacteria were recovered from sediment samples pre- treated with skim milk/HEPES and UV irradiation on a mannitol-based agar medium. A total of 183 actinobacterial strains were isolated from two sediment samples. Dereplication methods produced 42 distinct groups, with members of the genera Blastococcus, Salinispora and Streptomyces as the major clusters. Nineteen actinobacterial strains were identified as novel species belonging to seven genera (Agromyces, Blastococcus, Glycomyces, Mycobacterium, Nocardiopsis, Nonomuraea and Streptomyces) and one novel genus based on 16S rRNA gene sequence analyses. Strains TPS16, TPS81 and TPS83 were identified based on polyphasic data to be novel species belonging to a novel genus within the family Nocardiopsaceae, as proposed in this study as Marinitenerispora sediminis gen. nov., sp. nov. Crude extracts from strain TPS83 was found to inhibit the growth of Staphylococcus aureus, Bacillus subtilis and Providencia alcalifaciens. Hierarchical clustering of the bioactivities of an active fraction revealed a unique BioMap (antibiotic mode of action) profile, which is closely related to fosfomycin. Two compounds, nocapyrone R and methylpendolmycin, were purified from the active fraction that was eluted with 80% methanol/ water solvent system. This result showed that strain TPS83 could be a novel source of nocapyrone R and methylpendolmycin. Whole genomes of novel strains TPS2, TPS3, TPS16, TPS81 and TPS83 were sequenced and analysed. Prediction of biosynthetic gene clusters (BGCs) from the whole genome sequences revealed involvement of BGCs in biosyntheses of various types of secondary metabolites belonging to type I- and type II- polyketide synthases (PKS) as well as non- ribosomal peptide synthases (NRPS), which were associated with antimicrobial, anti-viral, anti- tumour and anti- parasitic activities. The NRPS gene coding for methylpendolmycin/ pendolmycin was found to be present in the genomes of TPS16 and TPS81, which are clonal strains of TPS83. This study is also the first to report novel Blastococcus strains (TPS166, TPS357, TPS418, TPS448 and TPS459) isolated from tropical marine sediment. Phylogenetic analysis based on 16S rRNA gene sequences showed that these strains could be putatively assigned to two different novel Blastococcus species.